2020
DOI: 10.24176/pro.v3i2.5333
|View full text |Cite
|
Sign up to set email alerts
|

The Presence of Collaboration Skill in Elt Class

Abstract: One of the skills that must be possessed in the 21st century is collaboration skill. It requires teachers to present or provide it in the learning process, so that later students are expected to be able to implement it in their real life. The study reported in this paper aims to describe the implementation of collaboration skill in the process of teaching and learning. The data collected by means of close-ended questionnaires and guided interview that were administered to 125 freshman students of the English E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…To them, if students exhibit these pointers, 21st century collaboration is being achieved. Moreover, Sudinpreeda et al (2020) confirmed that it is noteworthy for EFL teachers to utilize more suitable directions and apply limitations on how they are performed to be able to integrate the rudiments of collaboration in contemporary classrooms. Lailiyah et al (2021) disclosed that one way of supporting operative group work among students in higher education is for instructors to construct learning experiences consisting of varied teaching methodologies.…”
Section: Collaboration In Eltmentioning
confidence: 64%
“…To them, if students exhibit these pointers, 21st century collaboration is being achieved. Moreover, Sudinpreeda et al (2020) confirmed that it is noteworthy for EFL teachers to utilize more suitable directions and apply limitations on how they are performed to be able to integrate the rudiments of collaboration in contemporary classrooms. Lailiyah et al (2021) disclosed that one way of supporting operative group work among students in higher education is for instructors to construct learning experiences consisting of varied teaching methodologies.…”
Section: Collaboration In Eltmentioning
confidence: 64%